The impact of Basel III on the return on equity of the European banking sector - Duarte, José Maria (2022)
In recent years, regulation on banking institutions has been increasingly strict and evolving in order to mitigate events such as the 2008 financial crisis. After the crisis, it was realised that regulation at the time was not enough, as financial institutions lacked liquidity and had high financial leverage. Thus, the Basel Committee on Banking Supervision launched the Basel III Accord. With the introduction of this accord, several studies pointed out that it would affect banking Return on Equity (ROE). This study aims to assess the impact of Basel III variables on banking ROE in the European system, as well as to analyse the evolution of the variables that compose it. Through the literature review it was possible to identify which variables make more sense for the study. In order to produce this work, different complementary methods were used. In a more quantitative part, data was taken from the European Central Bank database. A multiple linear regression with standard robust errors was applied to these data. In order to complement the study, it was conducted interviews with experts in the field. The results indicate that credit risk has a positive impact on ROE, on the other hand, risk-weighted assets and the common equity tier 1 ratio show a negative impact on ROE. Analysing the variables, the main results indicate an significantly decrease on non-performing loans, as well as a strengthening of capital and the growth of more secure assets on banks' balance sheets.